Estimation of a term structure model of carbon prices through state space methods: The European Union emissions trading scheme. (22nd October 2020) - Aspinall, Thomas; Gepp, Adrian; Harris, Geoff; Kelly, Simone; Southam, Colette; Vanstone, Bruce
Abstract: This study models the term structure of the European Union Emissions Trading Scheme. The one‐factor geometric Brownian motion model of Abadie and Chamorro is replicated using the data now available and then compared with a two‐factor short‐term/long‐term (STLT) stochastic model. The STLT model has the better statistical fit to the term structure of European Union Allowances (EUAs). A real options analysis of the value of the option to retrofit carbon capture and storage shows that forecasting phase four EUAs with the STLT model almost triples the estimated project net present value and lowers investment trigger prices by approximately 24 percent.